Penguatan Karakter Pancasila Melalui Dasa Darma Pramuka di Era Digital - Zuhroh, Fadhilah; Apriani, Firza; Yurniwati, Yurniwati; Imaningstyas, Imaningtyas (SAP (Susunan Artikel Pendidikan), 2024)
Students' character is starting to fade due to the digital era, therefore it is necessary to develop character in accordance with the Pancasila Character. This research aims to analyze the implementation of scout activities at SDS Pantai Indah as an extracurricular program in strengthening the character of Pancasila in the digital era. The research was carried out in January - May 2024. The research method used was descriptive qualitative by collecting data through observation, interviews and documentation. The results of the research show that scout activities at SDS Pantai Indah focus on building the character of students based on the basic principles of Scouting, with an emphasis on the values of Pancasila. It was found that scout activities have significant benefits in developing students' character, such as thinking positively, speaking politely and politely, and being able to be responsible. Apart from that, the implementation of structured and varied scout activities helps in strengthening Pancasila values among students. These findings contribute to further understanding of the role of scouts in character education and instilling Pancasila values in the digital era. Therefore, it is recommended that schools continue to encourage and improve scouting programs in order to obtain optimal benefits in building the characters of students.